CODE-MIXING IN PRETTY LITTLE LIARS OF INDONESIAN TV SERIES (EUFONI: Journal of Language, Literary, and Cultural Studies, 2021)
This paper aims to analyze the types of code-mixing and the function of code-mixing through utterances by the casts of the Pretty Little Liars Indonesia TV Series in episodes 1 and 2. This research uses the descriptive qualitative method. The object of this research is code-mixing found in the Pretty Little Liars Indonesia TV Series in episodes 1 and 2. The data collection technique is the observation of the cast conversations in the Pretty Little Liars Indonesia TV Series.  The data were analyzed based on Muysken (2000) theory for the types of code-mixing and the theory of Hoffman (1991) for the function of code-mixing. The results showed there are 35 data of code-mixing. The kinds of code-mixing found in this research are Insertion, Alternation, and Congruent Lexicalization. There are 18 data of Insertion, 12 data of Alternation, and 5 data of Congruent Lexicalization. The second results for the function of the code-mixing showed that there are 26 data of Talking about a particular topic, 3 data of Being emphatic about something, 2 data of Interjection, 3 data of Intention of clarifying the content of speech for the interlocutor, and 1 data of Repetition used for clarification. The dominant function of code-mixing in this analysis is Talking about a particular topic.